Crucial Cell Signaling Compounds Crosstalk and Integrative Multi-Omics Techniques for Salinity Stress Tolerance in Plants - Singhal, Rajesh K.; Saha, Debanjana; Skalicky, Milan; Mishra, Udit N.; Chauhan, Jyoti; Behera, Laxmi P.; Lenka, Devidutta; Chand, Subhash; Kumar, Vivek; Dey, Prajjal; Indu,; Pandey, Saurabh; et al. (Frontiers in Plant Science, 2021)
In the era of rapid climate change, abiotic stresses are the primary cause for yield gap in major agricultural crops. Among them, salinity is considered a calamitous stress due to its global distribution and consequences. Salinity affects plant processes and growth by imposing osmotic stress and destroys ionic and redox signaling. It also affects phytohormone homeostasis, which leads to oxidative stress and eventually imbalances metabolic activity. In this situation, signaling compound crosstalk such as gasotransmitters [nitric oxide (NO), hydrogen sulfide (H2S), hydrogen peroxide (H2O2), calcium (Ca), reactive oxygen species (ROS)] and plant growth regulators (auxin, ethylene, abscisic acid, and salicylic acid) have a decisive role in regulating plant stress signaling and administer unfavorable circumstances including salinity stress. Moreover, recent significant progress in omics techniques (transcriptomics, genomics, proteomics, and metabolomics) have helped to reinforce the deep understanding of molecular insight in multiple stress tolerance. Currently, there is very little information on gasotransmitters and plant growth regulator crosstalk and inadequacy of information regarding the integration of multi-omics technology during salinity stress. Therefore, there is an urgent need to understand the crucial cell signaling crosstalk mechanisms and integrative multi-omics techniques to provide a more direct approach for salinity stress tolerance. To address the above-mentioned words, this review covers the common mechanisms of signaling compounds and role of different signaling crosstalk under salinity stress tolerance. Thereafter, we mention the integration of different omics technology and compile recent information with respect to salinity stress tolerance.